Tinjauan Penelitian Global: Analisis Bibliometrik Tren Manajemen Mutu dalam Pendidikan Tinggi Selama 20 Tahun Terakhir - Muthahharah Thahir (Journal of Education and Teaching (JET), 2025)
This study presents a comprehensive bibliometric analysis aimed at elucidating the evolving trends in quality management within higher education over the past two decades. Drawing upon a diverse array of scholarly literature sourced from Scopus databases, the analysis encompasses a broad spectrum of publications spanning from 2003 to 2023. From the search results, there were a total of 915 publications which were processed and visualized using VOS viewer and Bibliophagy software. By examining scholarly contributions globally, the study identifies Germany, the United States, and India as the leading countries in this research area. Analysis of publication sources reveals that journals such as Total Quality Management and Business Excellence and Quality Assurance in Education are the most prolific in disseminating research findings on this topic. Through keyword co-occurrence analysis, the study delineates five primary thematic clusters. These findings underscore the diverse and global nature of research efforts aimed at enhancing quality management practices in higher education. The article not only maps the existing research landscape but also offers valuable insights and actionable strategies for educators, policymakers, and researchers.